Don't tell the Nazis - Skrypuch, Marsha Forchuk (Scholastic Press, 2021)
In Ukraine, 1941, Krystia goes from living under the cruel occupation of the Soviets to the just-as-cruel occupation of the Nazis, even though some of her neighbors welcome the Germans as liberators. Then, Krystia's Jewish friend Dolik warns that their new rulers will bring even worse days, and after the Nazis frame the Jewish citizens for murders and force them into a ghetto, Krystia tries to do what she can to help Dolik and his family hide.